2009
DOI: 10.1038/aps.2009.90
|View full text |Cite
|
Sign up to set email alerts
|

Early onset Paget's disease of bone caused by a novel mutation (78dup27) of the TNFRSF11A gene in a Chinese family

Abstract: Aim: A previous study showed that individuals of Japanese descent affected by early onset familial Paget's disease of bone (PDB) carried a 27-bp duplication at position 75 (75dup27) in the TNFRSF11A gene encoding RANK. Here we report the identification of a novel mutation (78dup27) in exon 1 of TNFRSF11A in a Chinese family with early onset PDB. Methods: We conducted clinical and genetic studies in a non-consanguineous Chinese family with early onset PDB. The entire coding region of TNFRSF11A was amplified and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…(30) There is also expansion of tubular bones in the hands, and striking sclerosis and widening of the maxilla and mandible. (27) Consideration of PDB2 as a distinct entity gained support in 2009 when Ke et al (35) reported a Chinese kindred with clinical features like Japanese PDB2, (27) but manifesting somewhat later in life, also with a 27-bp but novel tandem duplication (78dup27) in TNFRSF11A that would insert a unique nonapeptide into the signal sequence of RANK.…”
Section: V) Discussionmentioning
confidence: 99%
“…(30) There is also expansion of tubular bones in the hands, and striking sclerosis and widening of the maxilla and mandible. (27) Consideration of PDB2 as a distinct entity gained support in 2009 when Ke et al (35) reported a Chinese kindred with clinical features like Japanese PDB2, (27) but manifesting somewhat later in life, also with a 27-bp but novel tandem duplication (78dup27) in TNFRSF11A that would insert a unique nonapeptide into the signal sequence of RANK.…”
Section: V) Discussionmentioning
confidence: 99%
“…Heterozygous insertion duplication mutations located within the signal peptide region of the RANK gene have been identified as the cause of these diseases. FEO is associated with an 18-base pair (84dup18) tandem duplication leading to an additional six amino acids in the RANK protein, ePDB with an insertion of 27 bp (75dup27 or 78dup27), leading to an additional nine amino acids and ESH with a 15 bp duplication (84dup15), adding five amino acids to RANK [48][49][50][51].…”
Section: Paget's Disease and Related Disorders Hyperactive Osteoclastsmentioning
confidence: 99%
“…Three rare familial and autosomal dominant skeletal dis orders have been described: familial expansile osteo lysis (FEO), 34,35 expansile skeletal hyperphosphatasia 36 and early onset Paget's disease, 37,38 which exhibit some charac teristics of classic Paget's disease. Each of these disorders develops as a consequence of different insertion mutations in the TNFRSF11A gene, which result in increased osteo clast activity.…”
Section: Autosomal Dominant Skeletal Disordersmentioning
confidence: 99%
“…36 Early onset Paget's disease has been described in one Japanese kindred 37 and in one Chinese kindred. 38 In the Japanese kindred, a 27 bp duplication was identified in exon 1 (75dup27) and in the Chinese kindred the 27 bp duplication in exon 1 extended from base 78 (78dup27). Affected individuals in the Japanese kindred experienced hearing impairment, tooth loss, skeletal enlargement and deformity in the second or third decade of life.…”
Section: Autosomal Dominant Skeletal Disordersmentioning
confidence: 99%